Single embryo transfer and multifetal pregnancy reduction: perception and attitude of women seeking assisted reproduction in Nigeria - Aziken, M. E.; A., Osaikhuwuomwan J.; I., Iribhogbe O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In-vitro fertilization (IVF) is associated with increased multiple pregnancy and its attendant complications. This study evaluates the attitude and acceptance of single embryo transfer (SET) and multifetal pregnancy reduction (MFPR) by clients assessing assisted reproduction in this region. Methods: A cross sectional survey of patients selected for IVF was conducted. Information on demography, knowledge of IVF procedure and their perception, attitude and acceptability of multiple pregnancy as well as their knowledge, attitude and perception to single embryo transfer and multifetal pregnancy reduction were extracted for statistical analysis. Results: Seventy-three women participated in the study. The mean age was 39 years and mean duration of infertility was 8.6 years. Only 3 (4.1%) respondents agreed to have SET as the overwhelming majority (70) 95.9% preferred 2 or more and they felt the more number of embryo transferred the better the chances of achieving pregnancy. Similarly most respondents, 38.4% (28) did not accept MFPR. Most respondents considered age (63%) and duration of infertility (78.1%) as major influencing factor for rejecting SET. Over 75% of respondents said they will still accept multiple embryos transferred despite knowledge of the possible complications. Conclusions: While most infertile women in our sub region appear to recognize the risks with multiple pregnancy, they are less interested in SET or MFPR because they perceive more embryos transferred as a means to maximize treatment outcome. Government funding, client education and a blastocyst transfer protocol may improve acceptability as well as overall preference for less number of embryos transferred in our environment.